INNOVATIVE PROCESSES IN THE RUSSIAN PHARMACEUTICAL MARKET - E. A. Bykova (Вестник университета, 2020)
The definitions the concepts of “innovations” and “innovation process” have been adduced, general assessment of the position of the Russian Federation in the world in terms of investment in scientific and technical research and developments (R & D) has been given, the most investment areas in terms of the volume of expenditures on scientific and technical research and development (R & D) have been highlighted . Key arguments that justify the need for innovative development of the pharmaceutical industry in Russia have been presented. The state and structure of the pharmaceutical market in Russia have been considered, the factors of transition of the pharmaceutical industry to an innovative course of development have been specified. Clear results of the implementation of the strategy for the development of the pharmaceutical industry until 2020 have been emphasized. Examples of implementation of the innovation management mechanism at the level of a separate domestic company Biocad have been given.